MEMAHAMI PROSEDUR DAN PERSYARATAN ZAKAT - Nurhadi Wiraatmaja (AL-ILMU, 2023)
This abstract discusses the importance of understanding the procedure and requirements of zakat. Zakat is a religious obligation in Islam that plays a significant role in building social justice and economic blessings. This abstract explains how to properly understand the procedure and requirements of zakat, starting from determining the nisab (minimum threshold) to calculating and distributing zakat correctly. By gaining a clear understanding of the zakat procedure, individuals will be able to fulfill their zakat obligation accurately and contribute to the desired social and spiritual goals. Keywords: Zakat, procedure, requirements